PENGARUH PEMBERIAN TUGAS RUMAH MIND MAP SEBELUM PENERAPAN MODEL PEMBELAJARAN AKTIF GIVING QUESTION AND GETTING ANSWER TERHADAP KOMPETENSI BELAJAR PESERTA DIDIK DI SMPN 27 PADANG - Threea Lestari; Helendra Helendra; Ristiono Ristiono; Sa'diatul Fuadiyah (Bioilmi: Jurnal Pendidikan, 2020)
Students at SMPN 27 Padang tend to be passive when the learning process takes place which results in low learning outcomes of students in natural science subjects. This study aims to determine the effect of giving home assignments in the form of Mind Map prior to the application of the Giving Question and Getting Answer (GQGA) active learning model on science learning competencies in the aspects of knowledge and attitudes of students in class VIII of SMP Negeri 27 Padang. This research is a Quasi-Experimental study and uses the Control Group Posttest Only Design. The study population was all students of Class VIII SMP Negeri 27 Padang. The technique used is Purposive Sampling. The control class uses the Direct Intruction learning model and the experimental class uses the active learning model Giving Question and Getting Answer by giving home assignments in the form of a Mind Map. The research instrument used was a test of learning outcomes and attitude assessment in the form of an observation sheet. T test results are known that the knowledge competency of tcount>ttable (4.99>1.67), and the results of the t test of competency attitude known tcount>ttable (6.36>1.67). This shows that the hypothesis is accepted. So, it can be concluded that the assignment of homework in the form of Mind Map prior to the application of the active learning model Giving Question and Getting Answer (GQGA) significantly influences the science learning competence in the aspects of knowledge and attitudes of students.